The Effect of Facilities and Service Quality on Visitor Satisfaction at Polbeng Business Expo Chapter Two - Feby Emy Tiana; M. Alkadri Perdana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Business Expo serves as an effective promotional platform that supports the growth of Micro, Small, and Medium Enterprises (MSMEs) while facilitating direct interaction between exhibitors and visitors. The success of a Business Expo is determined not only by the number of participants and visitors but also by visitor satisfaction with the facilities and services provided throughout the event. This study aims to analyze the influence of facilities and service quality on visitor satisfaction at Polbeng Business Expo Chapter Two. A quantitative approach with an associative research design was employed. Data were collected through questionnaires distributed to 100 visitors selected using incidental sampling and analyzed using multiple linear regression with SPSS version 31. The findings reveal that facilities have a positive and significant effect on visitor satisfaction (β = 0.475; p < 0.001), while service quality also has a positive and significant effect (β = 0.434; p = 0.001). Simultaneously, both variables significantly influence visitor satisfaction, with an R² value of 0.808, indicating that 80.8% of visitor satisfaction is explained by facilities and service quality. These findings provide practical recommendations for improving future Business Expo events through enhanced facilities, responsive services, and continuous visitor-oriented event management strategies